Effect of Macro Environment on the Development of College English Teachers’ Information-based Teaching Ability - Guo-rong, Shen (International Journal of Emerging Technologies in Learning (iJET), 2018)
The macro environment of teachers’ professional development involves many factors, including the policies, rules and regulations and the actual development needs of teachers. In terms of the ecological system of information technology, from the macro, the factors influencing teachers’ survival state includes policy system and teachers training. Based on the questionnaire surveys of three universities with different degrees of information technology development, the effect of macro environment on the development of college English teachers’ information-based teaching ability is studied and proper suggestions are put forward.